Activity-based Learning in Tamil Nadu– the Teacher's attitude - Anandh, S.; Raja, B. William Dharma (THE PRIMARY TEACHER, 2010)
In the context of improving the quality of primary education, a new attempt has been made in Tamil Nadu by the introduction of Activity-based Learning (ABL) in the teaching-learning process. The effectiveness of ABL depends primarily on how the teachers handle the ABL classes which mainly reflect their attitude towards ABL. So far only a few studies have been reported on the attitude of teachers towards ABL. The main objective of this research is to explore the attitude of primary school teachers towards ABL. The study was conducted on a sample of 200 teachers in the Palayamkottai Urban area schools of Tirunelveli district in Tamil Nadu using a researcher made tool. The key variables taken for this study include age, educational qualification, teaching experience, field exposure, student strength, school category, etc. The data analysis was done using SPSS version 11 for windows using T-test and F-test. The findings of the study revealed that primary school teachers, in general, share the same level of positive attitude towards ABL. It was also found out that teachers working in middle and higher secondary schools have a decreased level of positive attitude towards ABL than those working in primary schools